Conceptualizing degrees of theory of mind - Conway, J; Bird, G (National Academy of Sciences, 2018)
Successful navigation of the social world requires making accurate inferences about the contents of other people’s minds, being able to represent in one’s own mind the thoughts, beliefs, and intentions of another. This “theory of mind” (ToM) ability allows us to explain and predict others’ behavior in terms of their mental states (1). As reported in PNAS, Bio et al. (2) show that when prompted to adopt the visual perspective of a cartoon agent participants demonstrated the same spatial bias as when processing objects from their own perspective. Interestingly, this effect occurred only when the cartoon agent held a false belief about the location of an object, due to its having moved while the agent’s view was blocked by a barrier. When the agent held a true belief about the location of the object, either because he had witnessed it move or it never moved from its original location after the barrier appeared, participants’ own spatial bias had no effect on perspective taking (see Fig. 1A for a description of the experimental paradigm). Bio et al. (2) conclude that when representing others’ true beliefs, compared with their false beliefs, social cognition may be engaged to a lesser extent or not at all. This study is important because it may provide an answer to one of the most challenging questions in current ToM research: What is it to represent mental states to a greater or lesser degree?